The Effect of LED Lighting on Lettuce Growth in a Vertical IoT-Based Indoor Hydroponic System - Kuankid, Sanya; Aurasopon, Apinan (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Indoor vertical hydroponics is one of the most recent agricultural technologies to be introduced as it is a method of growing plants in vertically stacked layers using water and nutrient solution instead of soil. When cultivating such a system, the technique used to utilize and maintain the quality of water and nutrients is critical for plant growth. Additionally, the use of LED growth lights has a significant effect on plants. Despite developments in LED lighting and IoT-based smart agriculture systems, there is a lack of information on the use of LED lighting for hydroponically grown crops in vertical culture, due to the fact that vertical agriculture is a relatively new field of study. Thus, the aim of this research was to develop an IoT-based agricultural system to automated control LED-based artificial lighting on crop cultivation, as well as to explore the effects of different LED light on plant growth. In terms of the IoT-based system, numerous sensors were installed and monitored to measure the pH, EC, and other parameters. Using the Blynk application, those who can remotely control the LEDs and monitor the entire sensor and actuator. As for the effects of LED light, particularly the red and blue light, we utilize a case study of three LED grow light models from the manufacturer as light treatments for cultivating green leaf lettuce (Lactuca sativa). The result showed that increased R light (R/B = 2:1) resulted in an increase in plant height, leaf width, and leaf length on both harvesting days (10 and 20 DAT). The lettuce plant shape and size signify that the lettuces in each tier are of good standard and comparable in size.